Developmental Regulation of Corneal Protective Mechanisms. - Canner, James. (2017)
Abstract: As the cornea is exposed to damaging environmental insults, such as ultraviolet (UV) irradiation and noxious chemicals, it has evolved mechanisms to protect itself. Previous work in our laboratory identified one mechanism of protection against UV irradiation, which involves the sub-cellular localization of ferritin to the nuclei of corneal epithelial (CE) cells. Ferritin is localized to the nucleus by the action of a tissue specific transporter, ferritoid, where together they form nuclear complexes that protect the DNA from UV-induced damage. Furthermore, the developmental production of ferritoid and ferritin is regulated by systemic factors generated in the embryo. In the present study, we examined the ability of systemic factors to increase ferritoid and ferritin synthesis in corneal organ cultures. The addition of the thyroid hormone thyroxine, or serum, to the cultures resulted in increased protein levels for both ferritoid and ferritin, determined by immunofluorescence and Western Blot. For ferritoid, the increase in production appears to be controlled by a transcriptional mechanism, as a large increase in mRNA levels was observed, while ferritin was regulated predominately at the translational level. These results recapitulate the developmental regulation of ferritoid and ferritin synthesis in the CE. The cornea is densely innervated with nociceptive nerve endings to detect injurious chemicals. One class of molecules that are present on nerve endings to detect noxious chemical stimuli are the transient receptor potential (TRP) channels. Given the importance of these channels to detecting deleterious agents, we examined the ability of corneal-derived signals to control the synthesis of TRP channels in neurons. During in vivo development, TRPA1 mRNA levels increased in the ophthalmic lobe of the trigeminal ganglia (OTG), which contains the cell bodies of the corneal nerves, as corneal innervation progressed, and in a cornea-OTG co-culture system, the cornea increased TRPA1 in the OTG. Furthermore, culturing OTG with NT3 significantly increased TRPA1, while inhibiting corneal-derived NT3 with a function blocking antibody significantly reduced TRPA1 levels. The ability of NT3 to regulate TRPA1 diminished as the embryo aged, and a synergistic increase in TRPA1 was observed when NT3 stimulation was coupled with Ret receptor activation.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: Thomas Linsenmayer.; Committee: John Castellot, James Schwob, Beverly Rubin, and Ilene Gipson.; Keyword: Cellular biology.